An integrative review of South African cancer nursing research published from 2002-2012 - Johanna Maree; Shelley Schmollgruber (AOSIS, 2014)
Background: This integrative review aimed to quantify the publication output of South African cancer nursing research conducted between 2002 and 2012 and to identify key trends relevant to cancer nurse researchers. Objectives: To describe the publication output of cancer nursing research in terms of the journals of publication, authors, focus, participants and methods used, to explore whether the published work was funded and to assess the quality of the studies published. Methods: An integrative review was conducted using the key words South Africa in combination with cancer nursing and oncology nursing to search the databases Pubmed, PsycINFO, CINAHL, Sabinet, Web of Science, Medline and OvidSP. A data extraction sheet was developed to document the required information from each paper and all publications were reviewed independently by the authors. Results: A total of 181 publications for potential inclusion were identified and 26 papers were included in this review. Cervical cancer, specifically the prevention of this disease, was the most popular diagnostic focus and theme of investigation. Most of the studies were descriptive and none of the studies met the criteria of the highest quality. Conclusion: Nursing added to the body of knowledge regarding the primary and secondary prevention of cancer. There is a need for work on both men and women diagnosed withthe most common cancers, as well as the family and care giver. There is also a need for multidisciplinary work using complex interventions focusing on symptom management to improve patient outcomes.